METHOD FOR MEASURING ERROR ESTABLISHMENT IN 5-AXIS MILLING MACHINES WITH A TOUCH PROBE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The present paper proposes a method for measuring and compensating for error establishment. The measurement is done with a touch probe and the measuring program is a macro program. A mathematical model was developed to experimentally determine the error of non-alignment of the axis of rotation of the workpiece with the physical axis of rotation of mass C. A virtual approach to compensate for the error of establishment by using a postprocessor for the particular machine was also proposed.